1994
DOI: 10.1007/bf02015442
|View full text |Cite
|
Sign up to set email alerts
|

Wilms' tumor arising in a multicystic kidney

Abstract: We describe a child with Wilms' tumor (WT) which occurred in an unequivocal multicystic dysplastic kidney (MDK). We indicate a current nonsurgical approach to MDK, but stress the probable malignant degeneration of blastemal cells, the need to search carefully for the WT in the MDK, and the necessity on 3-monthly follow-up US studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…There were reports on the association of WT with MCDK, primarily based on case studies and small series (Table 1 [21–28]). Evidence supporting these case reports is often incomplete and not supported by outside pathological review [3].…”
Section: Resultsmentioning
confidence: 99%
“…There were reports on the association of WT with MCDK, primarily based on case studies and small series (Table 1 [21–28]). Evidence supporting these case reports is often incomplete and not supported by outside pathological review [3].…”
Section: Resultsmentioning
confidence: 99%
“…Pediatric renal tumors are rare, but not an insignificant portion of pediatric neoplasms being strongly associated with abnormal blastogenetic processes. 3,46 It has been suggested that the risk of developing Wilms' tumor increases with childhood insecticide exposures. 16 In addition, parental pesticide/herbicide exposures before birth (pre-partum) increase the risk of developing Wilms' tumors.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some exceptional complications of the MCK such as hypertension (cured after nephrectomy) [1] and malignant degeneration [4,11,12].…”
Section: Discussionmentioning
confidence: 99%